FIQH EKOLOGI MEMBANGUN FIQH EKOLOGIS UNTUK PELESTARIAN KOSMOS - Ridwan, Ridwan (Mazahib, 2013)
I should say that according to Islam, everything in the universe is created by God. It is God Who adorns the skies with the sun, the moon and the stars, and the face of the earth with flowers, trees, gardens, orchards, and the various animal species. It is again God Who causes the rivers and streams to flow on the earth, Who upholds the skies (without support), causes the rain to fall, and places the boundary between night and day. The universe together with all its richness and vitality is the work and art of God, that is, of the Creator. We are God’s vicegerents on the earth; it has been given us in trust. Just as we are not the lords of nature and the world, so the world is not our property which we can dispose of as we wish or as we are able. Nature was created by God and it belongs to God. Everything in nature is a sign of God’s existence.The article should tried to the readers on islamic studies that Islamic maintsream doctrine one of the most important was fiqh event regognized as fiqh civilization, but it has stagnance of the Islamic jurist progress to creat of jurisprudence until today, its impact for the habitual of moslems community all the corner of the world didn’t recognized as well as Islamic pillars and the five destination of shariah (maqashid ash syari’ah), as a moslem prominent thinker Yusuf Qardhawi added it one more as became hifdz al bi’ah. Nowdays, Islamic jurisprudence very compatible to creat new stream on fiqh as wellknown an ecological fiqh. Fiqh’s views basicly on the environment, cosmos ethic and earth conservation.